Herakleios, der schwitzende Kaiser Die oströmische Monarchie in der ausgehenden Spätantike - Viermann, Nadine (Millennium-Studien / Millennium Studies, 2021)
Focusing on the rule of Heraclius (610-643), this study examines the development of the Byzantine monarchy at the threshold between antiquity and the Middle Ages. It shows how the reigning Emperor responded to the domestic and external political challenges that endangered his rule and brought the Byzantine Empire to the brink of collapse.